Decision Making in an Organizational Setting: Cognitive and Organizational Influences on Risk Assessment in Commercial Lending - McNamara, Gerry; Bromiley, Philip (Academy of Management Journal, 1997)
Although management researchers would like to understand management decisions related to risk, almost all previous research on risk has used either experiments or aggregate corporate data rather than data from actual business decisions. In this initial research on risk in actual business decisions, we examined the risk assessments bankers assigned to commercial borrowers. We tested hypotheses derived from research in strategy, finance, and behavioral decision theory in order to assess the influence of both organizational and cognitive factors on the likelihood of risk assessment errors. Although we found that both organizational and cognitive factors influenced risky decision making, when both were present, organizational factors appeared to overwhelm cognitive biases.